2019
DOI: 10.1007/s10096-019-03769-8
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic and medical needs for therapeutic drug monitoring of antibiotics

Abstract: Therapeutic drug monitoring (TDM) of antibiotics has been practiced for more than half a century, but it is still not widely applied for infected patients. It has a traditional focus on limiting toxicity of specific classes of antibiotics such as aminoglycosides and vancomycin. With more patients in critical care with higher levels of sickness severity and immunosuppression as well as an increasingly obese and ageing population, an increasing risk of suboptimal antibiotic exposure continues to escalate. As suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
50
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 56 publications
0
50
1
Order By: Relevance
“…meropenem) and TDM has been more recently explored. 8,[14][15][16] Moreover, clinical studies associated with pharmacokinetic modelling and simulations have shown the importance of TDM to guide therapy with meropenem, treating many bacterial infections. 6,17,18 Hence, this literature review aims to assess the data available about meropenem TDM in clinical practice and how it helps to increase clinical and microbiological outcomes and to decrease possible adverse effects.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…meropenem) and TDM has been more recently explored. 8,[14][15][16] Moreover, clinical studies associated with pharmacokinetic modelling and simulations have shown the importance of TDM to guide therapy with meropenem, treating many bacterial infections. 6,17,18 Hence, this literature review aims to assess the data available about meropenem TDM in clinical practice and how it helps to increase clinical and microbiological outcomes and to decrease possible adverse effects.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…The SFPT-SFAR suggested TDM guidelines concern, not only the patient’s conditions (i.e., ICU patients with expected beta-lactam PK variability and/or patients with clinical signs potentially related to beta-lactam toxicity; critically ill patients undergoing RRT), the PK parameters to be evaluated according to different modalities of administration (i.e., plasma trough concentration in case of intermittent administration, plasma steady-state concentration in case of continuous administration), the timing (24 to 48 h after the onset of treatment; after any change in dosage; in the event of significant change in the patient’s clinical condition), the kind of tissues (e.g., in the case of central nervous system infection, on blood and cerebrospinal fluid samples collected concomitantly), but also the modality of measurements (i.e., a validated chromatographic method). In relation to this last recommendation, it has to be considered that the method most commonly used for TDM involves immunological assaying that is less laborious compared with high-performance liquid chromatography (HPLC) technology even though less accurate [ 116 ].…”
Section: What Can Be Done For Icu Septic Patients In Order To Applmentioning
confidence: 99%
“…Most drug dosages were defined in healthy adults during the drug development phase [ 11 ] by assessing the condition of a selective group of patients. However, these characteristics are not representative of all the patients who use these drugs, due to PK variability [ 12 ].…”
Section: Therapeutic Drug Monitoring (Tdm)mentioning
confidence: 99%
“…Monitoring techniques include single or mass-coupled chromatographic methods with a variety of detectors, including ultraviolet or fluorescent detectors (specified below) and immunoassays [ 10 , 11 ]. Many of these techniques have been approved by the Food and Drug Administration (FDA) of the United States [ 12 ].…”
Section: Introductionmentioning
confidence: 99%